Meiotic inhibition of bovine oocytes in medium supplemented with a serum replacer and hormones: effects on meiosis progression and developmental capacity - Sa Barretto, Leticia Siqueira [UNESP]; Dias Caiado Castro, Viviane Sgobbi [UNESP]; Garcia, Joaquim Mansano [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Cambridge University Press, 2011)
Aiming to improve the developmental competence of bovine oocytes during meiotic block, this study evaluated the effects of a serum replacer (Knockout SR(R)) and hormones (gonadotropins and estradiol) supplementation of prematuration medium (TCM119 with 0.5 mM IBMX [IBMX group] or 25 mu M roscovitine [ROSC group]) on the kinetics of oocyte nuclear maturation and embryo development. Most IBMX and ROSC oocytes prematured for 8 h culture remained in the GV stage (70.3% and 73.1%, respectively; p > 0.05) similar to Control 8 h (63.5%) and to control immature oocytes (Control 0 h, 92.5%). After prematuration for 16 h, no oocytes remained in the GV stage at similar rates to those recently aspirated (p < 0.05); GV rates in ROSC (32.4%) were higher (p < 0.05) than in the Control 16 h group (8.6%), but similar (p > 0.05) to IBMX (9.7%). After in vitro maturation (IMV) for 24 h, metaphase II (MII) rates for oocytes prematured during 8 h were similar (p > 0.05) between control and treatments (65.0-71.7%). Similarly, MII rates oocytes prematured during 16 h were similar (p > 0.05) between all groups (45.9-60.4%). Cleavage rates (67.8-78.2%), embryonic development in day-7 (25.0-35.6%) and hatching rates in day-8 (2.5-11.3%) oocytes blocked during 8 h were similar for all groups (p > 0.05). Results indicate that addition of Knockout SR(R) and hormones to meiotic block culture with IBMX and roscovitine negatively affected meiotic arrest, but did not impair oocyte nuclear maturation and acquisition of developmental competence.
Keywords: Cattle; IBMX; Knockout serum replacer; In vitro maturation; Meiotic arrest; Roscovitine